Crosstalk between Statins and Cancer Prevention and Therapy: An Update - Beniamin Oskar Grabarek; Dariusz Boroń; Emilia Morawiec; Piotr Michalski; Veronica Palazzo-Michalska; Łukasz Pach; Barbara Dziuk; Magdalena Świder; Nikola Zmarzły (Pharmaceuticals, 2021)
The importance of statins in cancer has been discussed in many studies. They are known for their anticancer properties against solid tumors of the liver or lung, as well as diffuse cancers, such as multiple myeloma or leukemia. Currently, the most commonly used statins are simvastatin, rosuvastatin and atorvastatin. The anti-tumor activity of statins is largely related to their ability to induce apoptosis by targeting cancer cells with high selectivity. Statins are also involved in the regulation of the histone acetylation level, the disturbance of which can lead to abnormal activity of genes involved in the regulation of proliferation, differentiation and apoptosis. As a result, tumor growth and its invasion may be promoted, which is associated with a poor prognosis. High levels of histone deacetylases are observed in many cancers; therefore, one of the therapeutic strategies is to use their inhibitors. Combining statins with histone deacetylase inhibitors can induce a synergistic anticancer effect.